The Geomorphology of Submarine Channel Systems of the Northern Line Islands Ridge, Central Equatorial Pacific Ocean - Gardner, James V.; Peakall, Jeffrey; Armstrong, Andrew A.; Calder, Brian R. (Frontiers in Earth Science, 2020)
More than 844,000 km2 of the northern Line Islands Ridge mapped with multibeam bathymetry and backscatter provide unprecedented views of the geomorphology of this isolated area in the central equatorial Pacific Ocean. A compilation of all available multibeam data in the area reveals six extensive submarine dendritic channel systems that encompass a combined drainage area that exceeds 60,000 km2. The channel systems occur in a predominately carbonate environment and are the longest calciclastic submarine channel systems mapped in the oceans to date. The channel systems occur in a carbonate-dominated region well above the carbonate compensation depth and have developed into the surface of basins that are surrounded by small guyots and seamounts that make up a discontinuous rim around the summit of the northern Line Island Ridge. The channels have mostly straight or gently curved well-developed tributaries and main reaches. Although the Line Island Ridge has been dated at 86 to 68 Ma old, the channels occur on the surface and are not buried by any significant sediment accumulations. Levees are very rare along the channel banks and no bathymetric expression of submarine fans was found where the channels exit onto the adjacent abyssal basins. There is sparse evidence of landslide deposits throughout the ridge although the flanks of the guyots exhibit numerous headwall scarps. The presence of plunge pools below the northwest escarpment, together with well-defined channels meters to hundreds of meters deep relative to the surrounding seafloor, suggests the channels might be relatively recent (perhaps late Neogene or even younger) features developed long after the ridge subsided more than a kilometer below sea level.